2017
DOI: 10.1080/01635581.2017.1299880
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle of Bioelectrical Impedance Analysis as Prognostic Factor in Palliative Care Patients at the National Cancer Institute in Mexico

Abstract: Patients with advanced cancer often experience symptoms of disease and treatment that contribute to distress such as weight loss, which is present in up to 85% of cancer patients. Palliative care in these patients focuses on care aimed at improving quality of life. Phase angle (PA) is obtained by bioelectric impedance analysis (BIA) and is associated with cellular function. It is considered a reliable marker of malnutrition. A low PA may suggest deterioration of the cell membrane, which in palliative patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
0
21
0
3
Order By: Relevance
“…The association between undernutrition and morbidity and mortality is known and widely documented in the adult population 7,25,26,34,[41][42][43][44][45] ; however, there is a lack of literature that demonstrates this association, evaluated particularly by body composition indicators, in sick and critically ill children. Thus, despite having several limitations, our study reinforces the importance of nutrition assessments in critically ill children and suggests that body composition may be useful not only for nutrition diagnosis and monitoring, but also for an additional indicator in estimating death risk and PICU LOS in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The association between undernutrition and morbidity and mortality is known and widely documented in the adult population 7,25,26,34,[41][42][43][44][45] ; however, there is a lack of literature that demonstrates this association, evaluated particularly by body composition indicators, in sick and critically ill children. Thus, despite having several limitations, our study reinforces the importance of nutrition assessments in critically ill children and suggests that body composition may be useful not only for nutrition diagnosis and monitoring, but also for an additional indicator in estimating death risk and PICU LOS in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate HR was 0.85 (95% CI 0.72–0.99, p = .048) . A separate study in Mexico that included 628 palliative outpatients also identified phase angle ≤4° to be a significant prognostic marker (HR 1.9, 95% CI 1.6–2.4, p < .0001) .…”
Section: Discussionmentioning
confidence: 94%
“…Davis et al examined phase angle in 50 patients with advanced cancer from inpatient units with a median survival of approximately 2 months, and reported that a higher phase angle had a nonsignificant trend toward longer survival (univariate HR 0.81, 95% CI 0.66–1.01, p = .57; multivariate HR 0.79, 95% CI 0.61–1.01, p = .064) . In another study, Perez Camargo et al enrolled 452 patients hospitalized in a palliative care unit, and found that a phase angle of ≥4° was associated with longer survival (median 86 days vs. 163 days, p > .0001) . Because the BIA device used in this study required patients to be able to stand, patients with poor Karnofsky Performance Status ≤40% or delirium were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The selected papers were all published within the last 14 years, and most were performed on outpatients and conducted in the United States, Mexico, and South Korea . Five studies were prospective, and the others were retrospective . The age of the population included in the studies varied between the fifth and sixth decade of life.…”
Section: Resultsmentioning
confidence: 99%
“…One study was exclusively with colorectal cancer patients, 1 with pancreatic cancer patients, and 2 studies with lung cancer patients . For studies that included different cancer types, digestive tract cancer was the most common type (Table ).…”
Section: Resultsmentioning
confidence: 99%